A descriptive analysis of 2020 California Occupational Safety and Health Administration covid-19-related complaints. (March 2022) - Thomas, Marilyn D.; Matthay, Ellicott C.; Duchowny, Kate A.; Riley, Alicia R.; Khela, Harmon; Chen, Yea-Hung; Bibbins-Domingo, Kirsten; Glymour, M. Maria
Abstract: COVID-19 mortality has disproportionately affected specific occupations and industries. The Occupational Safety and Health Administration (OSHA) protects the health and safety of workers by setting and enforcing standards for working conditions. Workers may file OSHA complaints about unsafe conditions. Complaints may indicate poor workplace safety during the pandemic. We evaluated COVID-19-related complaints filed with California (Cal)/OSHA between January 1, 2020 and December 14, 2020 across seven industries. To assess whether workers in occupations with high COVID-19-related mortality were also most likely to file Cal/OSHA complaints, we compared industry-specific per-capita COVID-19 confirmed deaths from the California Department of Public Health with COVID-19-related complaints. Although 7820 COVID-19-related complaints were deemed valid by Cal/OSHA, only 627 onsite inspections occurred, and 32 citations were issued. Agricultural workers had the highest per-capita COVID-19 death rates (402 per 100, 000 workers) but were least represented among workplace complaints (44 per 100, 000 workers). Health Care workers had the highest complaint rates (81 per 100, 000 workers) but the second lowest COVID-19 death rate (81 per 100, 000 workers). Industries with the highest inspection rates also had high COVID-19 mortality. Our findings suggest complaints are not proportional to COVID-19 risk. Instead, higher complaint rates may reflect worker groups with greater empowerment, resources, or capacity to advocate for better protections. This capacity to advocate for safe workplaces may account for relatively low mortality rates in potentially high-risk occupations. Future research should examine factors determining worker complaints and complaint systems to promote participation of those with the greatest need of protection. Highlights: COVID-19 mortality disproportionately affected specific occupations and industries. Cal/OSHA workplace complaint system may indicate poor workplace safety during the pandemic. Overall, complaints varied markedly by industry and rarely resulted in inspection or citation. High COVID-19-related complaint rates did not align with the highest COVID-19 death rates. Complaints filed to Cal/OSHA may better reflect employee resources than COVID-19 risk.